The relationships between land transportation and ambient air quality - Seah, Jolene Shi Hui. (2011)
This project studies the relationships between land transportation and ambient air quality in Singapore's context. The Motor Vehicle Emission Simulator (MOVES) version 2010a was used to model the baseline situation as well as scenario 1. MOVES was not used for scenarios 2a and 2b because electric fuel type data cannot be imported into MOVES and CNG data is not available in the MOVES database. Scenario 3 was analysed using mathematical calculations.